Advantages of Database Management System in Cloud Infrastructure - pandey, Rajneesh kumar; singh, Yashwant kumar; Milan, Ram (IJRDO -Journal of Computer Science Engineering, 2017)
The challenge of building consistent, available, and scalable data managementsystems capable of serving peta bytes of data for millions of users has confrontedthe data management research community as well as large internet enterprises. ACloud database management system is a distributed database that deliverscomputing as a service instead of a product. It is the sharing of resources,software, and information between multiple devices over a network which ismostly the internet. It is expected that this number will grow significantly in thefuture. As a result, there is a growing interest in outsourcing databasemanagement tasks to third parties that can provide these tasks for much lowercost due to the economy of scale just like putting it into the cloud. The cloud isused as astorage location and database can be accessed and computed from anywhere. Thelarge number of web application makes the use of distributed storage solution inorder to scale up. It enables user to outsource the resource and services to thethird party server. In this paper, we discuss the recent trend in cloud service basedon database management system and offering it as one of the services in cloud.We also proposed an architecture of cloud based on database managementsystem.